Energy efficient routing in delay tolerant network - Opoku, Michael (2014)
Delay Tolerant Networks (DTNs) are networks that have intermittent connectivity due to mobility of the devices in the network (nodes), low communication range, low node population and limited energy sources. Successful message delivery in DTNs depends on the number nodes in a network, which is sometimes challenged by the high rate of dead nodes. This study looked at the energy awareness of DTN routing protocol by performing experiments using the Opportunistic Network Environment (ONE) Simulator. Protocol performance was analysed using metrics like messages delivered, overhead ratio, average latency and success ratio. The experiments showed that Energy Spray and Wait (ESnW) routing protocol perform efficiently by delivering 111 messages, with an overhead ratio of 11.17 and a success ratio of 0.27 compared to Spray and Wait in a network of 100 nodes. The protocol also recorded a success ratio of 0.48 with no dead nodes in the network when the message creation interval for nodes was between 50 to 60 seconds. However, ESnW had a higher delay (32% more than SnW) because the protocol used alternate routes to select nodes with more battery to relay messages. The results showed that Energy Spray and Wait is an efficient DTN routing protocol due to the high success ratio and the low number of dead nodes it generates in an energy constrained network.